2022
DOI: 10.1029/2021gh000544
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationships Between the Geospatial Distribution of Cancer Incidence and Estimated Pesticide Use in the U.S. West

Abstract: In recent years, several studies have explored the geospatial distribution of cancer incidence across the United States at state (Siegel et al., 2018) and county (Boscoe & Johnson, 2014;Farazi et al., 2018) levels of resolution, reflecting a growing recognition of the connections between geography and health. While these studies found statistically significant differences among states and regions, they did not attempt to relate those findings to environmental factors. Recently, studies have begun to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Comprehensive knowledge about pesticide use is important for better linking and understanding pesticide use and its impact on environmental health. It is also essential to relate the application of these chemicals with human health outcomes (see, e.g., Joseph et al 2022. ).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive knowledge about pesticide use is important for better linking and understanding pesticide use and its impact on environmental health. It is also essential to relate the application of these chemicals with human health outcomes (see, e.g., Joseph et al 2022. ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the sampling of farm operations for the collection of pesticide application data, some pesticide-by-crop combinations are not enumerated for some regions. As a result, the pesticide estimate for a given area is calculated using estimates from neighboring geographic regions; this is referred to as the EPest-high estimate and, consistent with prior studies, will be used in the current study [ 40 ]. Finally, for California, pesticide use estimates are based on data obtained from the California Department of Pesticide Regulation, which requires the reporting of all pesticides applied in the state.…”
Section: Methodsmentioning
confidence: 99%
“…The utility of these data is clearly illustrated in two of our recent publications. Joseph, Propper, et al (2022), for example, used the current data to extract pesticide profiles of 11 states found in the Western United States at county scale. We found that these states are divided into two distinct groups: those that are herbicide‐dominated and those that are fumigant‐dominated (Figure 1).…”
Section: Figurementioning
confidence: 99%